Proposta de atividade epilinguística para o ensino de concordância verbal - Viana Lopes, Gustavo Henrique; Custódio Filho, Valdinar (Educação, Escola & Sociedade, 2023)
The objective of this study is to propose an activity for teaching 3rd person plural verbal agreement, a linguistic phenomenon highly valued in Portuguese classes, which, if it does not occur according to the standard norm, constitutes a stigmatizing factor of social distinction. In this context, it is important that the verbal agreement approach is given in a more productive way, presenting epilinguistic activities, which excel in reflection and awareness of how linguistic phenomena occur. Furthermore, considering that verbal agreement is a variable phenomenon in Brazilian Portuguese, it is important that it be approached according to the assumptions of the pedagogy of linguistic variation, which legitimizes the norm mastered by students and uses it as a starting point for the acquisition of prestigious norms. This study is relevant because it proposes material aligned with innovative linguistic theories and, therefore, with official guidelines present in documents such as PCN (1998) and BNCC (2017).